Up the agency - Mayle, Peter (St. Martin's Press, 1993)
Before his glorious retreat to Provence, delightfully chronicled in his best-sellers A Year in Provence and Toujours Provence, Peter Mayle made his career in advertising, beginning as a copywriter and finishing thirteen years later as a creative director ("I think I was also a vice president," he writes "but I never had the cards printed"). Up the Agency is his caustic valentine to the culture of Madison Avenue, where the tribal customs and rituals are as wondrous to behold as the sights on any anthropological expedition.